(untitled) (Medical Forum Monthly, 2024)
Objective: The objective of the current Randomized control trial is to compare the postoperative sensitivity among Flowable composite and flowable Giomer in NCCL Study Design: Randomized control trial study Place and Duration of Study: This study was conducted at the Operative department of PIMS Islamabad from December 2023 to February 2024. Methods: The 60 participants were equally divided into two groups. Group 1 have patients whose NCCLs were restored with flowable composite and in group 2 flowable Giomer. Both groups were compared for postoperative sensitivity at days 3, 7 and 21. Results: The study included 60 participants, with 30 individuals assigned to each group. Group 1 had a mean age of 46 years (SD = 14.0), while Group 2 had a mean age of 40 years (SD = 11.0). Teeth distribution comprised 46.67% molars and 16.27% incisors. The mean sensitivity at day 0 was 1.9 for Group 1 and 0.9 for Group 2. At day 21, postoperative sensitivity was 1.00 for Group 1 and 0.93 for Group 2. The chi-square test was utilized to assess associations between variables, such as age, tooth type, and sensitivity levels, across both groups and there was a significant difference among both groups. (P≤0.05) Conclusion: Giomer shows a notable decrease in postoperative sensitivity compared to flowable composite, as observed on days 3, 7, and 21 in the Schiff cold test. These results suggest Giomer's have efficacy in managing postoperative sensitivity in non-carious cervical lesion treatments which enhancing evidence-based restorative dentistry and improving patient outcomes.